Konsep Perwalian Perkawinan Abdülaziz Bayindir Perspektif Hukum Keluarga Islam - Wapa Atoillah, Sohibul; Asmuni, Ahmad; Rofii, Ahmad (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2023)
Abdülaziz Bayindir, a Professor in the field of Islamic Law, expressed a different opinion from the schools of jurisprudence regarding the position of guardians in marriage. He even criticized the methodology of extracting law from the arguments used. He expressed this opinion, among others, in Mafhāi>m Yanbaghi an Tusahah fi Dau’al-Qur’ān al-Karim. He, there, revealed legal arguments systematically and how the law was taken from the argument. On the other hand, at the same time also providing criticism and rebuttal to the arguments and legal arguments put forward by the jurists of the school of jurisprudence in the theme of jurisprudence discussion.The research method in this study is qualitative with a normative approach, namely analyzing data using an argument or rule approach that guides human behavior. This approach is used to analyze how Abdülaziz Bayindir’s concept, perspective and relevance to Islamic Family Law in Indonesia and the world.The purpose of the research in this journal is to adopt how Abdülaziz Bayindir's legal thinking, then more specifically on the concept of his marriage guardianship, then viewed from the perspective of Family Law applied in several Muslim countries in the world.